MARKETING STRATEGY FOR THE LAUNCH OF A NEW PRODUCT IN THE CZECH MARKET FOR A STARTUP COMPANY - Singh Mejia, Darshan Nicolas Teji (2017)
The aim of this thesis is to develop the marketing strategy for Company X to use for launching a new product (plantain snack) in the Czech market. The thesis will be divided into two parts: theoretical and practical (analytical). The theoretical part will cover the basic information relevant to the theory product launch, marketing strategy, and market analysis. The practical section will focus on establishing the most appropriate marketing strategy for a product launch to be used by the Company X.This thesis will be based on primary and secondary information sources (research based on professional literature) about the current market situation, customers, and competitors, (marketing research), the state of the market as well as an analysis of competitors.The practical part of the thesis will consist of the SWOT analysis of the new product/ company, internal documents of the Company X and promotional materials of both Company X and competitors, as well as an own marketing research material, in the form of focus groups.